Methyl-Deficient Transfer Ribonucleic Acid in Saccharomyces cerevisiae - Phillips, John H. (1969)
Methyl-deficient transfer ribonucleic acid (tRNA) is found in certain methionine auxotrophs of Saccharomyces cerevisiae during logarithmic growth (at one generation time before the late growth phase) and during residual growth in the absence of exogenous methionine. The former effect seems to be accounted for by the general increase in RNA synthesis that occurs at the time; there is no specific synthesis of tRNA in the absence of ribosomal RNA synthesis, nor is the methyl group deficiency limited to a single tRNA species. During methionine starvation, all species of tRNA are methyl-deficient, but this occurs only in strains with certain blocks in the methionine pathway. The kinetics of disappearance of the methyl group donor, S-adenosylmethionine, during starvation of D73 (which accumulates methyl-deficient tRNA), do not differ from other strains, but D73 loses the methylase inhibitor, S-adenosylhomocysteine, much more slowly.